2020
DOI: 10.3324/haematol.2019.240739
|View full text |Cite
|
Sign up to set email alerts
|

Why is it critical to achieve a deep molecular response in chronic myeloid leukemia?

Abstract: The primary goal of tyrosine kinase inhibitor (TKI) therapy for patients with chronic myeloid leukemia is survival, which is achieved by the vast majority of patients. The initial response to therapy provides a sensitive measure of future clinical outcome. Measurement of BCR-ABL1 transcript levels using real-time quantitative polymerase chain reaction standardized to the international reporting scale is now the principal recommended monitoring strategy. The method is used to assess early milestone responses an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 97 publications
1
8
0
Order By: Relevance
“…IRF4 expression tends to normalize in patients achieving MR. Interestingly, CML cases in MR4.5 and MR5 show comparable values to those in the HC group, while a mild downregulation is still evident in patients in MR3 and MR4. On the one hand, these findings are in line with the concept that patients achieving the greatest degree of MR are the best candidates for TKI discontinuation [15,23,24]; on the other hand, even a residual presence of the BCR-ABL transcript, as expressed by MR3 and, frequently, MR4, is associated with a significant IRF4 downregulation. A correlation analysis between the IS and IRF4 values confirmed this close association.…”
Section: Discussionsupporting
confidence: 80%
“…IRF4 expression tends to normalize in patients achieving MR. Interestingly, CML cases in MR4.5 and MR5 show comparable values to those in the HC group, while a mild downregulation is still evident in patients in MR3 and MR4. On the one hand, these findings are in line with the concept that patients achieving the greatest degree of MR are the best candidates for TKI discontinuation [15,23,24]; on the other hand, even a residual presence of the BCR-ABL transcript, as expressed by MR3 and, frequently, MR4, is associated with a significant IRF4 downregulation. A correlation analysis between the IS and IRF4 values confirmed this close association.…”
Section: Discussionsupporting
confidence: 80%
“…This suggests that a follow-up ≤60 months may be insufficient to adequately assess the proportion of patients achieving sustained DMR. However, the rate observed with bosutinib by five years was similar to imatinib by eight years, suggesting (with acknowledgement of caution in comparison across studies) that treatment with second-generation TKIs may allow patients to achieve a sustained DMR faster, as would be expected based on the earlier achievement of DMR with second-generation TKIs [ 15 ]. This study also confirmed the achievement of BCR::ABL1 transcript level ≤10% at three months as predictive of sustained MR 4 , as previously suggested in studies with other TKIs [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of AML samples remain cytokine-dependent for growth, and FLT3 inhibitors may target this necessary growth signal. Although we do not yet know whether the synergy we observed with the drug combination ex vivo will translate into more durable responses in patients, studies in other disease types suggest that treatments delivering deeper up-front responses often improve response duration 52,53 . Ultimately, this question will be best answered by evaluation in an early-stage clinical trial with accompanying monitoring of minimum residual disease.…”
Section: Discussionmentioning
confidence: 96%